Effects of Natural Atlantic Forest Regeneration on Soil Fauna, Brazil - Camara,Rodrigo (2018)
Abstract The stage of natural forest regeneration may influence soil fauna. This study aimed to test the hypothesis that there are differences in the structure and composition of the soil fauna communities between areas undergoing less advanced (LAS) and more advanced (MAS) stages of natural regeneration of Seasonal Semideciduous Forest at Pinheiral, RJ. Soil fauna was sampled using pitfall traps, during dry and rainy seasons. Total abundance, abundance of the saprophagous/predator group, mainly Formicidae, and the relative participation of Orthoptera were higher in MAS, while the relative participation of Acari, Araneae, Coleoptera, Diptera and the herbivorous group were higher in LAS, during both climatic seasons. Some taxonomic groups were restricted to one of the areas. Richness, evenness and diversity tended to present higher values in LAS (dry season). The higher complexity of the soil fauna community was correlated to the higher leaf litter standing stock in LAS.